Pengembangan Modul Praktikum Deviasi Dan Indeks Bias Prisma Berbasis Laboratorium Virtual - Olivia Betricha Gare; Jimmy Lolowang; Jeferson Polii (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2022)
Research is motivated by the lack of a virtual lab-based deviation and refractive index practicum module, so students are less experienced in using these tools while experimenting. This purpose of this research is to create a virtual lab-based module for prismatic deviation and refractive index. This research is developmental (Research and Development) using a 4D research model adopted from Thiagarajan model i.e. define, design, develop, and disseminate. The result of the group research receive an average value of 83.19%, so that the module is classified in the feasible/valid category. And in the student responses 58.35% said it was very useful (SB), 39.6% said it was useful(B), and 2.05% said it was less useful(KB), no one chose not useful(TB). Based on the result of the research, it can be concluded that a product in the form of a basic physics practicum module for the virtual laboratory-based prism deviation and refractive index tool was manufactured with good and appropriate qualifications.